Bone marrow-derived mesenchymal stem cells inhibit CD8+ T cell immune responses via PD-1/PD-L1 pathway in multiple myeloma. (7th May 2021) - Liu, Z; Mi, F; Han, M; Tian, M; Deng, L; Meng, N; Luo, J; Fu, R
Summary: High expression of the inhibitory receptor programmed cell death ligand 1 (PD-L1) on tumor cells and tumor stromal cells have been found to play a key role in tumor immune evasion in several human malignancies. However, the expression of PD-L1 on bone marrow mesenchymal stem cells (BMSCs) and whether the programmed cell death 1 (PD-1)/PD-L1 signal pathway is involved in the BMSCs versus T cell immune response in multiple myeloma (MM) remains poorly defined. In this study, we explored the expression of PD-L1 on BMSCs from newly diagnosed MM (NDMM) patients and the role of PD-1/PD-L1 pathway in BMSC-mediated regulation of CD8 + T cells. The data showed that the expression of PD-L1 on BMSCs in NDMM patients was significantly increased compared to that in normal controls (NC) (18·81 ± 1·61 versus 2·78± 0·70%; P  < 0·001). Furthermore, the PD-1 expression on CD8 + T cells with NDMM patients was significantly higher than that in normal controls (43·22 ± 2·98 versus 20·71 ± 1·08%; P  < 0·001). However, there was no significant difference in PD-1 expression of CD4 + T cells and natural killer (NK) cells between the NDMM and NC groups. Additionally, the co-culture assays revealed that BMSCs significantly suppressed CD8 + T cell function. However, the PD-L1 inhibitor effectively reversed BMSC-mediated suppression in CD8 + T cells. We also found that the combination of PD-L1 inhibitor and pomalidomide can further enhance the killing effect of CD8 + T cells on MM cells. In summary, our findings demonstrated that BMSCs in patients with MM may induce apoptosis of CD8 + T cells through the PD-1/PD-L1 axis and inhibit the release of perforin and granzyme B from CD8 + T cells to promote the immune escape of MM. Graphical Abstract: